2016
DOI: 10.1002/mame.201600094
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐Retarded Epoxy Resins with a Curing Agent of DOPO‐Triazine Based Anhydride

Abstract: A 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO)‐triazine based anhydride (2,4,6‐tris‐(DOPO‐methylformatephthalic anhydride‐phenoxy)‐1,3,5‐triazine (TDA)) is synthesized and used as a halogen‐free flame retardant co‐curing agent for diglycidyl ether of bisphenol A/methylhexahydrophthalic anhydride (DGEBA/MHHPA) system. The conjugation of anhydride group is increased by the utilization of TDA, leading to the reduction in the curing activation energy. The cured epoxy resin passes V‐0 rating of UL 94 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“… And, in general, anhydride and amine are two kinds of curing agents for EPs, the aromatic polyamine cured network structure with relatively low cross‐linking density, while the anhydride cured EPs have a larger amount of rigid, a higher glass transition temperature ( T g ), and lower curing shrinkage. Despite the fact that anhydride type is the second largest usage amount of curing agent for EPs, the research on the flame‐retardant modification of curing agent has rarely been reported up to now …”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“… And, in general, anhydride and amine are two kinds of curing agents for EPs, the aromatic polyamine cured network structure with relatively low cross‐linking density, while the anhydride cured EPs have a larger amount of rigid, a higher glass transition temperature ( T g ), and lower curing shrinkage. Despite the fact that anhydride type is the second largest usage amount of curing agent for EPs, the research on the flame‐retardant modification of curing agent has rarely been reported up to now …”
Section: Introductionsupporting
confidence: 91%
“…[34][35][36] Despite the fact that anhydride type is the second largest usage amount of curing agent for EPs, the research on the flame-retardant modification of curing agent has rarely been reported up to now. 37 In this work, we modified PEPA by reacting with trimellitic anhydride chloride (TMAC) and used the resulting anhydride product (PEPA-TMAC) as a co-curing agent for EP. The chemical structure of PEPA-TMAC was characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and highresolution mass spectrum (HRMS).…”
mentioning
confidence: 99%
“…The T g was maintained below 350 °C, and significantly reduced above it. The T g reached the minimum value of 91.9 °C at 370 °C and then was increased above 370 °C probably because of crosslinking caused by Fries rearrangement and Kolbe–Schmitt rearrangement . The onsets of degradation points of PC/PP20 at 0.5 and 1 wt % loss were determined to be 285.7 and 326.7 °C, respectively (Figure S8).…”
Section: Resultsmentioning
confidence: 94%
“…In the past, bromine compounds were commonly used as flame retardants for polymers, but a number of products with bromine compounds have been restricted now owing to the probability of generating toxic and corrosive smoke during combustion. Many nonhalogen‐based compounds, such as phosphorus‐ or nitrogen‐containing additives, fillers, epoxy resins, and curing agents, have been investigated to improve the flame resistant properties of epoxy thermosets …”
Section: Introductionmentioning
confidence: 99%